Association of gestational weight gain patterns with preterm birth subtypes in a population based cohort study from China - Yiyang Guo; Kai Chen; Jin’e Zhang; Yiming Zhang; Zhiguo Xia; Yuji Wang; Xiaoxuan Fan; Xiaofeng Mu; Luli Xu; Chao Xiong; Aifen Zhou (Scientific Reports)
Abstract This study examined the association between gestational weight gain (GWG) patterns and preterm birth (PTB) subtypes using data from a registry system in Wuhan, China. A total of 57,138 women with live singleton births were included. Total GWG in the first and second trimesters was categorized as insufficient, appropriate, or excessive based on Chinese guidelines, and weekly early GWG (< 20 weeks; eGWG) was classified into Class I (< 100 g/week), Class II (100–399 g/week), and Class III (≥ 400 g/week). Multiple logistic regression analyses assessed the relationships between GWG patterns and PTB subtypes, including spontaneous PTB, medically indicated PTB, and preterm premature rupture of membranes (PPROM), and adjusted for covariates such as age, education, pregnancy, parity, and offspring sex. Subgroup analyses were conducted by pre-pregnancy BMI categories (underweight: <18.5 kg/m², normal weight: 18.5–23.9 kg/m², overweight/obesity: ≥24 kg/m²). Results showed that underweight women with excessive GWG or Class III eGWG had increased risks of all PTB subtypes. Normal weight women with excessive or Class III eGWG, as well as insufficient or Class I eGWG, exhibited elevated risks for all PTB types. Overweight/obesity women with insufficient or Class I eGWG were at higher risks for spontaneous PTB and PPROM. These findings underscore the importance of optimal GWG across all BMI categories to mitigate PTB risks, highlighting the need for tailored prenatal weight management strategies.